In Vitro Cytotoxicity of a New Nano Root Canal Sealer on Human Gingival Fibroblasts - Javidi, Maryam; Dastmalchi, Parisa; Zarei, Mina; Shayani Rad, Maryam; Ghorbani, Ahmad (Iranian Endodontic Journal, 2017)
Introduction: The aim of this in vitro study was to evaluate the cytotoxicity of a new nano zinc-oxide eugenol (NZOE) sealer on human gingival fibroblasts (HGFs) compared with Pulpdent (micro-sized ZOE sealer) and AH-26 (resin-based sealer). Methods and Materials: The Pulpdent, AH-26, and NZOE sealers were prepared and exposed to cell culture media immediately after setting, and 24 h and one week after setting. Then, the primary cultured HGFs were incubated for 24 h with different dilutions (1:1 to 1:32) of each sealer extract. Cell viability was evaluated by methyl thiazolyl diphenyl tetrazolium bromide (MTT) assay. The results were compared using two-way analysis of variance followed by Tukey’s post hoc test. The level of significance was set at 0.05. Results: All sealer extracts, up to 32 times dilutions, showed cytotoxicity when exposed to HGF immediately after setting. The extracts obtained 24 h or one week after setting showed lower cytotoxicity than extracts obtained immediately after setting. At all setting times, NZOE showed lower cytotoxicity than Pulpdent and AH-26. While one-week extracts of NZOE had no significant effect on the viability of HGF at dilutions 1:4 to 1:32, both Pulpdent and AH-26 decreased the cell viability at dilutions of 1:4 and 1:8. Conclusion: NZOE exhibited lower cytotoxicity compared to Pulpdent and AH-26 on HGF and has the potential to be considered as a new root canal filling material. Keywords: Cytotoxicity; Human Gingival Fibroblast; MTT assay; Nano; Sealer